The Relationship between Sport Education and Leadership in the Formation of Student Character - Siska Aprelyani (Siber International Journal of Sport Education, 2025)
Literature Review of the role of Sport Education and Leadership in improving Student Character Formation is a scientific article with the aim of analyzing whether Student Character Formation plays a role in Sport Education and Leadership. The qualitative approach method with the literature review method to explore and analyze the relationship between sport education, leadership and character formation. The results of this article are: 1) Sport Education plays a role in Character Formation, 2) Leadership plays a role in Character Formation. Apart from these 2 exogenous variables that influence the endogenous variable of Character Formation, there are still many other factors including the school environment, technology, education.